If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3q = 12 + -1q Solving 3q = 12 + -1q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add 'q' to each side of the equation. 3q + q = 12 + -1q + q Combine like terms: 3q + q = 4q 4q = 12 + -1q + q Combine like terms: -1q + q = 0 4q = 12 + 0 4q = 12 Divide each side by '4'. q = 3 Simplifying q = 3
| 7x+24=3x+112 | | 4t+2=17-t | | 4q+3=q+3 | | x^4-8x^3+x-8=0 | | 12-8x=39-29x | | 35+33x=11x+12+22 | | -143-9x=9x+9x | | 3a-1=a+7 | | 7a+2=10 | | 3+5u=2u+12 | | 2x+7x^2=8 | | 6m-1=m+9 | | 2x+7x=4 | | x^3-3x-18=0 | | 4x*57=3x-7 | | 2x+2x+2=0 | | -7r+5=5r+35 | | -7r+4=5r+35 | | 2x^2+2x-10=0 | | 2x(3x+3)=18 | | x-5x=-5,682 | | 4x-2=2x+14 | | 4x-8=8x | | 2x+3=15+x | | 56x+(-5x+9x)= | | -1-2x=3 | | 4(2a+-1)+5(4+-2a)-3a=-4(5+2a)-4 | | 0.41=0.07x | | -14=x+22 | | 0.41=0.07 | | x-8.8=-3.3 | | 0.44=0.07x |